Technology Entrepreneurship Project (ENT 600) : Panasonic Malaysia Sdn. Bhd / Mohammad Zailani Mohamad Zanawi - Mohamad Zanawi, Mohammad Zailani (2021)
Panasonic Corporation is a company that produces various types of home appliances and electrical products. Konosuke Matshushita founded Matshushita Electric Home Appliances Manufacturing Jobs in 1918. It is located in Selangor, Malaysia. One of the products produced by Panasonic Corporation is Panasonic fan. A fan is an electrical device that helps reduce heat and provide comfort. There are several types of fans produced by this company namely ceiling fan, table fan, standing fan and wall fan. The objective of this study is to analyse the problems faced by Panasonic Malaysia SDN. BHD. and provide better solutions and solve problems and give suggestions to companies in order to improve their company in the future. After doing company analysis, there are some issues that are based on 6-Blade Mondo Ceiling fan. The first problem is short motion sensor, the detect for start is slow. The second problem is easily replicated model that is many companies want to satisfy customers. The third problem is the demand is seasonal. Therefore, there are three solution suggested for all problems. The first solution is to increase the distance sensor Panasonic 6-Blade Mondo just can be detecting the sensor has so short. Another common setting for motion sensor fans is a fan distance detect. A good distance for most security fan applications is 4 to 4.5 meters for height and detection range 5 meters. The second solution is to use voice control important in the life of technology because people want to be easy anytime and everything. When the technology more sophisticated the people like use the product for the life. More technology sophisticated, more people like this. The last solution is remote-controlled ceiling fan it can gives the freedom to switch on/off and control the speed of your ceiling fan with minimum movement. This adds convenience and ease for them to control fans without assistance. Besides, this study came out with a proposal to choose one of the solutions. This study proposes to choose to produce making remote-control technology. This is because the function of remote-control technology easy to turn on or turn off the fan and control the speed of ceiling fan.